KAJIAN BUDIDAYA SAGU (METROXYLON SPP) RAKYAT DI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Bakhtiar Ruli Hrp; Ardian Ardian; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Meranti Islands District is one of the development areas of national food security as the biggest sago producer in Indonesia. The area of sago palm Meranti Islands District is 38 163 ha. Tebing Tinggi Subdistrict West has a land area of 2,573 hectares. This study aims to look at the differences sago cultivation techniques in wet and dry land in the District of West Tebing Tinggi, Meranti Islands. This research has been conducted in the district of West Tebing Tinggi, Meranti Islands regency in Riau province. Implementation of this research was conducted during one month is in September and October 2016. The method applied was a survey and observation. Determining soil sample in this study using the purposive random sampling method. The data collected in this study the primary data and secondary data. Data were analyzed by t-test in the form of quantitative and qualitative data is presented in Table. The results showed no significant impact, either care, maintenance, HPT control, time of harvest and only significant in the weed control. The type of sago in Sub Tebing Tinggi Southwestern namely tuni, ihur and molat and different harvested based on age, and through the development phase of the sago palm. Keywords : Study,Sago palm cultivation, People